Hubungan Beban Kerja dan Kejenuhan Kerja Terhadap Stres Kerja Perawat - Ardi ansyah; Kari yani (STIKES Citra Delima Bangka Belitung, 2022)
Work stress is pressure from work that can affect the psychology of workers. Several factors that cause work stress are workload and work saturation. The purpose of this study was to determine the relationship between workload and work saturation on nurses' work stress. This study uses a quantitative method with a Cross Sectional approach. The population in this study were nurses who served in the inpatient room as many as 120 people from 7 rooms. The sample in this study was 73 people with a sampling technique using Propionate Stratified Random Sampling. The research instrument used a questionnaire of work stress, workload and work saturation. This study uses statistical analysis using the Chi-Square test at a 95% confidence level (α = 0.05). The results of this study indicate that the nurse's workload has a p value = 0,585 and work saturation, p value = 1,000, has no significant relationship with nurses' work stress. Suggestions from this study are expected to be input for hospitals to determine steps in stress management or stress management for nurses.